2007
DOI: 10.3892/or.17.4.731
|View full text |Cite
|
Sign up to set email alerts
|

Association of extracellular matrix metalloproteinase inducer in endometrial carcinoma with patient outcomes and clinicopathogenesis using monoclonal antibody 12C3

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN) is a member of the immunoglobulin superfamily of adhesion molecules and has a role in the activation of several matrix metalloproteinases (MMPs). We evaluated whether EMMPRIN expression is related to tumor progression and patient outcome in human endometrial carcinoma. Paraffinembedded surgical tissue samples from 112 patients with endometrial carcinoma were stained with anti-EMMPRIN antibody (monoclonal antibody 12C3:MoAb 12C3) for immunohistochemical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Accordingly, emmprin expression has been found to be associated with known risk factors for breast cancer and with a poor prognosis of breast cancer patients [19]. In endometrial cancer, Ueda et al reported that high levels of emmprin expression had a significant association with recurrence [33]. However, the correlation between emmprin expression and survival has not been studied in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, emmprin expression has been found to be associated with known risk factors for breast cancer and with a poor prognosis of breast cancer patients [19]. In endometrial cancer, Ueda et al reported that high levels of emmprin expression had a significant association with recurrence [33]. However, the correlation between emmprin expression and survival has not been studied in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal squamous cell carcinomas (ESCC) (stage 3 and 4) and endometrial (97.3% incidence) carcinoma show significant upregulation of tissue expression of CD147, while CD147 is not expressed in the respective normal tissues [130,131]. CD147 holds promise as a reliable biomarker in cancer progression, showing a significant expression increase in carcinomas compared with sarcomas and normal epithelial tissues, as well as positively correlating with tumor recurrence and progression and negatively correlating to survival in breast cancer patients in a retrospective study [132].…”
Section: Cd147 and Cancermentioning
confidence: 99%
“…EMMPRIN, also called CD147 or basigin, is a cellular adhesion molecule involved in cell-cell and cell-ECM interactions (8–10). EMMPRIN is highly expressed on the surface of various malignant tumor cells compared with their normal counterparts (16,17) and is involved in tumor invasion and metastasis (14,18). Our previous study found that overexpression of EMMPRIN was a prognostic factor for patients with SACC and was positively associated with the perineural and perivascular invasion of SACC (11).…”
Section: Discussionmentioning
confidence: 99%